On an Inverse Scattering Problem for a Discontinuous Sturm-Liouville Equation with a Spectral Parameter in the Boundary Condition. (21st June 2010) - Mamedov, Khanlar R.
Abstract : An inverse scattering problem is considered for a discontinuous Sturm-Liouville equation on the half-line[ 0, ∞ ) with a linear spectral parameter in the boundary condition. The scattering data of the problem are defined and a new fundamental equation is derived, which is different from the classical Marchenko equation. With help of this fundamental equation, in terms of the scattering data, the potential is recovered uniquely.